Allergic rhinoconjunctivitis (a tool to help clinicians) - N. A. Aref’eva; V. V. Brzheskii; V. V. Vishnyakov; A. V. Emel’yanov; S. A. Karpishchenko; S. Ya. Kosyakov; A. S. Lopatin; D. Yu. Maichuk; Ya. A. Nakatis; I. V. Otvagin; G. Z. Piskunov; D. P. Polyakov (Oftalʹmologiâ, 2014)
Allergic rhinoconjunctivitis is a chronic inflammatory IgE-mediated reaction to relevant allergens encountering nasal mucosa and conjunctiva. Allergen-specific IgE binds to high-affinity Fcε receptors (Fcε RI) expressed by ocular and nasal mast cells. Therefore, nasal mucosa and conjunctiva have common mechanisms of antigen recognition. Detailed clinical history and examination provide correct diagnosis, relevant allergen identification, symptom severity assessment, and therapeutic algorithm. Recently, an assay for the measurement of specific IgE antibodies against numerous (120) allergens in human blood, ImmunoCAP, was developed. Conventional allergic rhinoconjunctivitis treatment includes allergen avoidance, pharmacotherapy, and allergen-specific immune therapy. Four major classes of drugs are used for the treatment, i.e., antihistamines, corticosteroids, mast cell stabilizers, and vasoconstrictor agents (or decongestants). Occasionally, muscarinic receptor antagonists, antileukotrienes, and immunemodulators are used. Therapeutic strategy is determined by the effect of a drug on certain symptoms and allergy clinical course, adverse reaction and complication risks, age limitations, and costs. Stepwise approach to the treatment of allergic rhinoconjunctivitis should be based onsymptom severity. Full-text clinical guidelines are available on the official website of Russian Rhinologic Society (http://www.rhinology.ru / index1. php?id_page = 3&id_text2 = 43&num_text2 = 1).